Ultrasonic evaluation of scrotal swellings - Misaki, T (Hinyokika kiyo. Acta urologica Japonica, 1985)
The diagnostic value of ultrasonography for 101 scrotal swellings of 94 patients was assessed. The 101 swellings showed sonographically 87 extratesticular, 11 testicular and 3 combined lesions. This sonography was concluded to be a satisfactory diagnostic aid for scrotal cystic lesions, testicular tumors and the localization of scrotal lesions